FORMULATION AND EVALUATION OF HERBAL EXFOLIATE FILM CONTAINING CYPHOMANRDA BETACEAE&PHASEOLUS MUNGO - PRIYA ABRAHAM, (International Journal of Pharma and Bio Sciences, 2013)
Exfoliation involves the removal of the oldest dead skin cells on the skins outermost surface to help maintain healthy skin. The most serious form of skin cancer is caused by excessive exposure to the sun (ultraviolet radiation). Skin cells that are damaged are at greater risk of becoming abnormal and cancerous. Herbal skin exfoliates enriched with flavanoids penetrate deep into the skin, nourishes it, and prevents photo damage such as discolouration and hyper pigmentation. Since herbal exfoliate shows a good antimicrobial and antioxidant activity, it shields the skin from environmental toxins, pollution and micro organism. Herbal exfoliation may also prevent skin cancer. Advantages of facial peel which Improves the texture of the skin, makes the skin healthy, makes the skin look more radiant, reduces appearance of wrinkles and fine lines, removes the dirt clogged in the pores, prevents acne and aging of the skin. Disadvantages mainly High price of some of the products and methods used to achieve it, exfoliation will lead to some initial redness to the skin, At the end of chemical peels, the skin will frost, with colors varying from a bright white to grey on the skin surface, plastic beads or polymer often used as exfoliates are not biodegradable where they remain in the soil or river for a very long time polluting the environment. Considering the above disadvantages, effort had been taken to formulate an herbal facial peel which is cheap, ecofriendly and effective on human skin without causing irritation. Cyphomandra&phaseolus genus belonging to the family Solanaceae whichare used for this studies.